2022
DOI: 10.1097/jcma.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with postoperative respiratory conditions and critical outcomes on pediatric liver transplantation: A single-center experience

Abstract: Background: Orthotopic liver transplantation (OLT) is an established therapeutic option for pediatric end-stage liver disease (PELD). The postoperative respiratory conditions of OLT recipients may be associated with subsequent clinical outcomes including length of stay (LOS) in the pediatric intensive care unit (PICU). This study aimed to characterize the postoperative respiratory conditions, associated factors, and outcomes after pediatric OLT. Methods: Clinical data of children receiving OLT from July 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…As a result, children are more vulnerable to perioperative lung injury than adults. Although studies have suggested that pretransplant PELD scores are associated with postoperative outcome indicators after liver transplantation [ 12 , 34 ], it was not observed in our study. This may be partly due to differences in study populations, clinical trial conditions, and surgical techniques.…”
Section: Discussioncontrasting
confidence: 80%
“…As a result, children are more vulnerable to perioperative lung injury than adults. Although studies have suggested that pretransplant PELD scores are associated with postoperative outcome indicators after liver transplantation [ 12 , 34 ], it was not observed in our study. This may be partly due to differences in study populations, clinical trial conditions, and surgical techniques.…”
Section: Discussioncontrasting
confidence: 80%
“…Therefore, more powerful and accurate biomarkers and/or clinical parameters are urgently needed to determine what situations may be associated with mortality as well as with developing post-resuscitation morbidity while surviving. [3][4][5] In theory, similar to all other diseases, [5][6][7][8][9] an early identification of risk factors associated with IHCA and an offering the prompt and effective treatment may decrease the IHCA -related morbidity and mortality. The recent publication in the last October issue of the Journal of the Chinese Medical Association entitled "Prognostic significance of the blood urea nitrogen to creatinine ratio in in-hospital cardiac arrest after targeted temperature management," attempted to use the simple parameters of blood urea nitrogen (BUN) to creatinine (Cr) ratio (BCR) to predict the neurological outcome at discharge among IHCA patients receiving targeted temperature management (TTM).…”
mentioning
confidence: 99%